Quality of Life of Family Caregiver of Cancer Patient: A Literatur Review - Nur Maziyya; Laili Rahayuwati; Ahmad Yamin (Journal of Nursing Care, 2018)
Background: Cancer is one of chronic diseases that require long-term care. Family as the closest one who lives with the cancer patient takes a leading role in providing care. It causes some impacts that possible happen to family caregiver (FCs) such as feeling burden and decreasing quality of life (QoL). Purpose: This literature review was conducted to describe findings from studies concerning QoL of FCs of cancer patients. Methods: This review used scoping review methods. Electronic literature searching was conducted using databases: Proquest, PubMed, Google scholar and Science Direct using keywords quality of life, family caregiver and cancer patient/terminal patient/terminally ill patient. Inclusion criteria were: research papers, focus on caregiver of cancer patient, peer-reviewed, and published between 2008-2018. Exclusion criteria was non-English papers and papers that discuss other than caregiver of cancer patients. There were a total of 45 papers retrieved; however, only 13 papers met the inclusion and exclusion criteria. Analysis was conducted using content analyses. Findings: Research about QoL of FCs of cancer patient have been done in some countries and used some different methodes. They showed that the primary FCs of cancer patient were spouses and had low QoL. Factors that associated with FCs’ QoL such as patients’ age and condition, spousal relationship, FCs’ religiousness, emotional distress, carigiving burden, lack of social support and satisfaction with care. Conclusions And Recommendations: FCs of cancer patients had low quality of life and caused by many factors. Further studies required to determine other factors from patients, FCs and environment that influence the FCs’ QoL.